Thin Metal Superlens Imaging in Nanolithography. (2nd May 2019) - Wang, Jing; Sheng, Yunlong
Abstract : Superlens imaging system in nanolithography can be regarded as a cascade of two F-P cavities, i.e., a superlens cavity and a dielectric cavity between superlens and introduced mask of high loss, and the transfer function of system is obtained by considering multiple reflections inside the two cavities. For the range of wavevector of interest, the typical high peak of transmission coefficient of superlens coincides with a local minimum of transmission coefficient of dielectric cavity. The peak of transfer function of system corresponds to the peak of transmission coefficient of dielectric cavity. Thin superlens imaging system in nanolithography is analyzed based on transfer function, which can be flattened by simply tuning transmission coefficient of dielectric cavity and superlens cavity. The results are further validated by Finite Element Method (FEM) simulations.